miRNA expression profile as a potential tool for discrimination between bacterial and interstitial cystitis - Peskar, Dominika; Kojc, Nika; Erman, Andreja; Boštjančič, Emanuela (Frontiers in Immunology, 2026)
IntroductionInterstitial cystitis (IC) is an aseptic chronic bladder inflammation of unknown etiology and poorly understood pathophysiology with symptoms resembling bacterial cystitis (BC). There is limited data about the contribution of regulatory microRNAs (miRNAs) in IC. The study aimed to identify differences in miRNA expression between mouse models of IC and BC to find potential miRNAs that would distinguish between the two types of cystitis and to evaluate the use of the mouse model of IC as a tool to study the pathogenic mechanisms of IC in humans.MethodsTwo mouse models were utilized: cyclophosphamide was used for induction of chronic aseptic cystitis, and uropathogenic E.coli for induction of acute bacterial cystitis. Potential regulatory miRNAs were selected based on publicly available human IC datasets and validated in mice. Quantitative PCR and RNA isolated from formalin-fixed, paraffin-embedded mouse bladder tissue were used. An enrichment analysis of the target mRNAs of the validated miRNAs was performed to suggest the differences in the possible mechanisms of inflammation between the IC and BC.ResultsWe observed differential expression of 20 of the 33 selected miRNAs in IC and BC compared to the control group, with 11 miRNAs showing the same trend of expression between mouse and human IC. There are 8 common reporter-assay (RA) validated targets (performed by others) of these miRNAs in mouse and human. Histopathological analysis of mouse IC and BC urinary bladders, miRNA expression analysis, and expression of their validated targets revealed significant differences between the urinary bladders of BC and IC mouse models. We identified miR-301a-3p as a possible marker of discrimination between two types of cystitis and its target gene, nuclear factor-κB (NF-κB) suppressing factor (NKRF).ConclusionOur results show that miRNA expression and its RA-validated targets, and enriched signaling pathways, differ between the two types of cystitis and might depend on the type of bladder inflammation. The mouse model of IC has some similarities with human IC, confirming that it is a useful tool to identify novel potentially discriminatory biomarkers between BC and IC, such as miR-301a-3p, and also potential therapeutic targets for IC (e.g., NKRF and NF-κB).